CeCl3⋅7H2O/SiO2 as an Efficient and Recyclable Catalyst for the Synthesis of Dihydropyrano[3,2-b]chromenediones - Chong Zhang; Yan Qu (Journal of Chemistry)
Dihydropyrano[3,2-b]chromenedione derivatives were synthesized in moderate-to-high yields in one-pot three-component reaction from the corresponding aromatic aldehydes, kojic acid, and dimedone, in the presence of catalytic amount of CeCl3⋅7H2O/SiO2 as a nontoxic, reusable, inexpensive, and easily available reagent, under solvent-free conditions.